(untitled) (Hematology Meeting Reports, 2009)
The Intergroupe Francophone du Myélome (IFM) has conducted studies of thalidomide as treatment for relapsed or refractory multiple myeloma (MM) and as first-line therapy. One study comparing two doses of thalidomide (100 vs 400 mg/d) in relapsed patients has not yet been analyzed. Another study testing low-dose thalidomide in combination with melphalan and prednisone (MP) in elderly patients (>75 years) with newly diagnosed MM is ongoing. Three studies are presented here. Of these, one phase 2 study in relapsed/refractory patients has already been published; the other two have been presented in meetings only.